SOFTWARE DESIGN OF DUAL CHANNEL POTENTIOSTAT SYSTEM FOR READING SCREEN PRINTED ELECTRODE ION SENSORS NA+ AND K+ IN BIOSENSOR RESEARCH - Hanif Adityo, Muhammad
The research group of the National Research and Innovation Agency (BRIN) in collaboration with Bandung Institute of Technology (ITB) and FK UHAMKA conducted research on ion sensors in the form of Screen Printed Electrode (SPE). This research is based on the needs of the FK UHAMKA research team to measure electrolytes in daily urine and study their relationship to the physiological conditions of the body. The focus of this research is on the correlation between sodium (Na+